2018
DOI: 10.1007/s00253-018-9167-2
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific affibody molecule targeting HPV16 and HPV18E7 oncoproteins for enhanced molecular imaging of cervical cancer

Abstract: High-risk human papillomavirus (HPV16 and HPV18) are now widely recognized as responsible for cervical cancer, which remains to be the most common gynecologic malignancy in women worldwide. It is well known that viral oncoproteins E6/E7 play key roles in HPV-associated cervical carcinogenesis. Thus, in vivo detection of the two oncoproteins may provide important diagnostic information influencing patient management. More recently, affibody molecules have been demonstrated to be a promising candidate for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Kinetic BIAcore analysis indicated that each of the Z LMP2A-N affibodies bound to LMP2A-NCD with affinities approximately 10 5 times higher than that of Z WT and reached the μM level, in accordance with previous studies of Z HPV16E7 384 25 , Z HPV16E7 384-Z HPV18E7 228 29 , and Z HPV16E7 affitoxin384 30 in our laboratory. Furthermore, according to IFA, the Z LMP2A-N affibodies could specifically bind to EBV-positive cell lines, and LMP2A-NCD and Z LMP2A-N affibodies were also co-localised in the juxtamembrane region.…”
Section: Discussionsupporting
confidence: 90%
“…Kinetic BIAcore analysis indicated that each of the Z LMP2A-N affibodies bound to LMP2A-NCD with affinities approximately 10 5 times higher than that of Z WT and reached the μM level, in accordance with previous studies of Z HPV16E7 384 25 , Z HPV16E7 384-Z HPV18E7 228 29 , and Z HPV16E7 affitoxin384 30 in our laboratory. Furthermore, according to IFA, the Z LMP2A-N affibodies could specifically bind to EBV-positive cell lines, and LMP2A-NCD and Z LMP2A-N affibodies were also co-localised in the juxtamembrane region.…”
Section: Discussionsupporting
confidence: 90%
“…Because of their small size, affibody can be synthesized or recombinantly expressed. Since the first construct HER2-targeting affibody molecule Z HER2:342 was produced and confirmed to bind to HER2-positive cancer cell lines [24], several similar affibody molecules targeting EGFR [23,24], HER3 [27,28], IGF-1R [42], HIV-1-gp120 [43] and HPV16E7 [30,31] have been reported and also applied to image several tumour-associated molecular targets, such as HER2 [25,44], EGFR [45,46], HER3 [47]. The first clinical imaging study on patients with breast cancer was conducted using HER2-specific affibody, which Mice bearing C666-1tumor grafts were intravenously injected with 100 nmol/kg Z142X, Z142, or an equal amount of control agents or the same volume of PBS every two days for 15 times via tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the target-binding of the selected Z EBVLMP-2 affibodies to EBV LMP-2, surface plasmon resonance (SPR) was performed on a ProteOn XPR36 system (Bio-rad, California, USA). The LMP-2 B-epitope fusion protein (1 nM) served as the ligand was immobilized onto the surface of carboxylate glucans in HTG sensor chip (Bio-rad), as described previously [30,31]. Subsequently, five or six concentrations of each affibody sample were prepared and injected over the chip surface to record sample binding to the surface.…”
Section: Surface Plasmon Resonance Analysismentioning
confidence: 99%
See 2 more Smart Citations